1976
DOI: 10.1029/jc081i024p04445
|View full text |Cite
|
Sign up to set email alerts
|

The barrow submarine canyon: A drain for the Chukchi Sea

Abstract: Oceanographic measurements made in the spring through holes in the ice in an area off Barrow, where the Barrow Canyon forms a sloping trough from the shallow Chukchi Sea into the deep Beaufort Sea, have revealed two interacting water movements: (1) a flow of highly saline water from the shallow Chukchi Sea into the Beaufort Sea through the Barrow Canyon and (2) an uprising of Atlantic water from the depths of the Beapfort Sea into the Barrow Canyon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…During the cold season (November–April), strong reversals (flow toward the south‐southwest) were common (Figure ). At C1, these periods of southwestward flow were often associated with inflow of relatively warm (>1°C) Atlantic Water (Ladd et al, ), and as observed by prior work (e.g., Aagaard & Roach, ; Bourke & Paquette, ; Garrison & Becker, ; Mountain et al, ; Woodgate et al, ). Ladd et al () also noted that the number of occurrences of Atlantic Water varied seasonally (usually occurring between October and May) and among years with 2010–2011 having more events (3) than the other years.…”
Section: Resultssupporting
confidence: 59%
“…During the cold season (November–April), strong reversals (flow toward the south‐southwest) were common (Figure ). At C1, these periods of southwestward flow were often associated with inflow of relatively warm (>1°C) Atlantic Water (Ladd et al, ), and as observed by prior work (e.g., Aagaard & Roach, ; Bourke & Paquette, ; Garrison & Becker, ; Mountain et al, ; Woodgate et al, ). Ladd et al () also noted that the number of occurrences of Atlantic Water varied seasonally (usually occurring between October and May) and among years with 2010–2011 having more events (3) than the other years.…”
Section: Resultssupporting
confidence: 59%
“…In late winter to early summer the situation is even less certain. The traditional view is that after the winter winds relax, much of the dense water from the eastern Chukchi Sea flows down Barrow Canyon and directly enters the interior Canada Basin [ Garrison and Becker , 1976; Weingartner et al , 1998]. However, dynamical constraints, supported by recent model results [ Chapman , 2000], suggest that a large fraction of the dense wintertime water approaching Barrow Canyon may not exit through the canyon, but instead might adjust to deeper isobaths and also turn eastward.…”
Section: Introductionmentioning
confidence: 99%
“…It is now commonly accepted that the cold halocline of the Arctic Ocean is predominantly maintained by lateral processes [ Aagaard et al , 1981]. In particular, dense water formed on the shelves is transported by a variety of processes into the interior basins [e.g., Garrison and Becker , 1976; Spall et al , 2008]. In the western Arctic much of this dense water emanates from the polynyas in the Chukchi Sea [ Cavalieri and Martin , 1994; Winsor and Björk , 2000].…”
Section: Discussionmentioning
confidence: 99%